Strategi Pengembangan Pariwisata Pantai Ngebum Kabupaten Kendal - Oktaviana Rahayu Jati Asmoro; Sri Rahayu (Teknik PWK (Perencanaan Wilayah Kota), 2019)
Tourism is a highly developing sector in Indonesia. Indonesia has so many tourism spots that its government is focusing on making policies on how to develop its tourism potentials. There are five things that need to be considered on tourism development, namely tourists, accessibility, tourist attractions, tourist accommodation, and promotions. Pantai Ngebum is one of many tourist sites in Kendal Regency. Pantai Ngebum has been opened as a tourism spot since 2010 but is still poorly managed independently by people of Mororejo Village where it is located. Due to its poor management, tourism facilities’ condition in Pantai Ngebum is considered low. On weekdays, Pantai Ngebum is usually visited by up to 100 people, but on weekends or holiday seasons the visitors could reach up to 1.600 people. Because of the high interest from the visitors, Pantai Ngebum is expected to improve its development so it can be one of Kendal Regency's top tourism sites. This research is aimed to find tourism development strategies in Pantai Ngebum using SWOT analysis.